Proses Pengolahan Limbah Jagung Menjadi Pupuk Organik Di Desa Wellulang Kecamatan Amali Kabupaten Bone - A.Besse Dahliana; Hujemiati Hujemiati; Yusnan Suyuti DM; Jumardi Jumardi (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Process of Processing Corn Waste into Compost Fertilizer in Wellulang Village, Amali District, Bone Regency. By students of the Yapi Bone College of Agricultural Sciences. The purpose of this training in making compost is to determine the process of processing corn waste into compost and the effect of compost on organic plants in Wellulang village, Amali district, Bone district. Corn waste processing starting from corn stalks that are no longer used are usually processed into compost. The trick is to pulverize corn and rice straw that has been harvested by chopping it with a machine and adding various types of mixed fertilizers. The process of mixing the ingredients in a balanced way, the dosage of raw materials, and the temperature of the composting process. Compost fertilizer can add organic matter to the soil, so that the soil will be able to hold water in sufficient quantities and can enrich microbes that are useful in breaking down soil organic matter, because organic matter is available to be processed into ready-to-absorb material, and the presence of microbes is expected to provide availability of elements that are absorbed in the colloid of the soil into nutrients for plant growth.